Analysis and design of a bill notification system using rapid application development - Harsih Rianto (Institute of Computer Science (IOCS), 2024)
The current billing management system at PT. Media Prima Jaringan is inefficient, leading to service disruptions and customer dissatisfaction. Despite data recording being assisted by a computer system, significant issues persist. Billing delivery to customers is still done manually by printing invoices, resulting in serious service disruptions. Customer complaints often arise due to discrepancies in billing amounts, late payments, and even service disconnections. Besides customer complaints, the company also incurs losses due to dissatisfied customers switching to other providers, resulting in subscription cancellations. Through the development of a billing notification system using the WhatsApp application, it is hoped that the company can expedite customer billing information. In developing the system, systematic stages are required to produce a good quality Information System that can be used by users. The fundamental stages in the System Development Life Cycle (SDLC) include planning, analysis, design, implementation, testing, and maintenance. One of the SDLC development models is Rapid Application Development (RAD). In addition to using the RAD model for system development, the author also utilizes the Unified Modeling Language (UML) as a tool in the design phase. The RAD approach enables the system to be developed within 45 days, with intensive discussions aiding quicker design completion. Upon implementation, company revenue increases, and customer complaints decrease, highlighting the system's effectiveness in improving service delivery and customer satisfaction